ปัญหาและแนวทางการพัฒนาการบริหารจัดการเพื่อส่งเสริมอาชีพ ด้านเกษตรอินทรีย์สําหรับเกษตรกรขององค์กรปกครองส่วนท้องถิ่น ในจังหวัดปราจีนบุรี - ฉิมมากูร, อารดา; ถนอมศรีเดชชัย, ชมัยภรณ์; วิรัชนิภาวรรณ, วิรัช (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
Objectives of this study were to investigate (1) administrative problems of organic agriculture occupational promotion; (2) administrative development guidelines of organic agriculture occupational promotion; and (3) factor effecting the success of administrative development guidelines of organic agriculture occupational promotion. The ITERMS concept consisting with 6 components was applied as the conceptual framework of this study. This study was designed as quantitative research using questionnaire as tools for data collection from 356 samples who were farmers residing in 4 Sub-district Administrative Organizations of Prachinburi Province. Statistics applied for data analysis were percentage, mean, and standard deviation. Research findings revealed that (1) the main administrative problem was the local administrative organizations in Prachinburi Province’s insufficient information dissemination of organic agriculture occupational promotion for farmers; (2) the significant administrative development guideline was the local administrative organizations in Prachinburi Province should designate more skilled personnel to implement organic agriculture occupational promotion for farmers; and (3) the factor effecting the success of the mentioned administrative development guideline was that the local administrative organizations in Prachinburi Province prioritize organic agriculture occupational promotion for farmers as their targeted goal of implementation.